From children's services to children's spaces : public policy, children and childhood - Moss, Peter, 1945- (RoutledgeFalmer, 2002)
At the turn of the millennium, attitudes and actions towards children are increasingly contradictory and complex. This work explores these apparent contradictions and complexities through a critique of the concept of children's services.